2018
DOI: 10.17116/hirurgia2018868
|View full text |Cite
|
Sign up to set email alerts
|

Intrapancreatic accessory spleen

Abstract: Described cases demonstrate difficulty of differential diagnostics of tumor - like mass. Neuroendocrine tumors, renal - cell cancer metastases, solid pseudopapillary neoplasms and accessory spleen can have similar CT-characteristics. In appearance of differential diagnostic difficulties minimally invasive surgical treatment has to be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Although previous studies have indicated that imaging data is an essential basis for diagnosing IPAS [7,36,37], in our case, CT, MRI, PET-CT, and EUS were not good for the differential diagnosis of IPAS. The previous studies found that IPAS should be considered when a smooth, round, solid hypervascular mass appears in the tail of the pancreas on abdominal CT [11,38].…”
Section: Discussioncontrasting
confidence: 86%
“…Although previous studies have indicated that imaging data is an essential basis for diagnosing IPAS [7,36,37], in our case, CT, MRI, PET-CT, and EUS were not good for the differential diagnosis of IPAS. The previous studies found that IPAS should be considered when a smooth, round, solid hypervascular mass appears in the tail of the pancreas on abdominal CT [11,38].…”
Section: Discussioncontrasting
confidence: 86%
“…Ultrasound examination, combined with CEUS, MRI and PET/CT revealed to be highly accurate methods in the diagnosis and differentiation of IPAS and small solid pancreatic tumors. [16][17][18][19][20] IPAS is an asymptomatic lesion and surgical treatment and histopathological confirmation may not be needed if diagnostic imaging highly suggests IPAS in children. There is significant importance in differentiating IPAS from pancreatic malignant tumors.…”
Section: Discussionmentioning
confidence: 99%